SUITABILITY OF THIN-LAYER DRYING MODELS FOR INFRARED DRYING OF PEACH SLICES - Doymaz, Ibrahim (WILEY, 2014)
The effect of different infrared power levels on drying kinetics of peach slices was investigated. The peach slices dried at 83, 125, 167 and 209W infrared power levels and constant slice thickness of 0.5cm. It was observed that drying characteristics of peach slices were greatly influenced by infrared power. To select the most appropriate thin-layer drying model for drying treatments, 15 mathematical drying models were fitted to the experimental data. Midilli etal. model satisfactorily described the drying kinetics of peach slices. Effective moisture diffusivity ranged from 1.68x10(-10) to 1.68x10(-9)m(2)/s and calculated using the Fick's second law. Activation energy was estimated by a modified Arrhenius-type equation as 4.49kW/kg. Practical Applications Drying is a very important preservation method that is used in the food industry. The basic objective in drying food products is the removal of water from fresh product reaching a level at which microbial spoilage is avoided. Infrared drying has gained popularity as an alternative drying method for a variety of agricultural products. Compared with hot air drying, infrared radiation drying offers many advantages such as greater energy efficiency, heat transfer rate and heat flux, which results in reduced drying time and higher drying rate. The main objectives of this study were to investigate the effect of infrared power on the drying rate and drying time, to fit the experimental data to different thin-layer drying models and to compute effective moisture diffusivity of peach slices. The present study is useful for producers of dried products.
Keywords: MOISTURE DIFFUSIVITY; KINETICS; HEAT; QUALITY; FRUITS; FRESH; Food Science & Technology